Abs. Issue 1 (November 2015) - Kashina, E.; Oshchepkov, D.; Shilov, A.; Antontseva, E.; Furman, D.; Mordvinov, V.
Abstract : Background: The environmental pollutant 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) is the most toxic among the dioxin xenobiotics and induces a broad spectrum of biological responses, including immunotoxicity and cancer[1] . Macrophages are very plastic cells and can acquire various functionally distinct phenotypes depending on the physiological context. They are key regulators of the innate immune response and determine the developmental thrust of the adaptive immune response. The action of TCDD on macrophages is unique in that carried out through a variety of pathways, inducing activation of a number of cytokines[2] . Our previous analysis showed that the list of such cytokines was not complete[3] . IL-12 family of cytokines is the key players in the regulation of T cell responses. Little is known of the effects that TCDD has on the expression of IL-12 family member's genes, such as IL12A, IL12B, IL27 and EBI3, which forms a critically important cytokines IL-12 and IL-27, secreted by human macrophages. In the present work, the effects of TCDD on expression of IL-12 family member's genes in human macrophages have been investigated. Results: To examine the effects of TCDD on the functional characteristics of macrophages, experiments have been conducted on the monocyte-like cell line U937 and primary human macrophages. Obtained data demonstrate functional activity of DREs in IL12A, IL12B and IL4 gene promoters via AhR signal pathway. The mRNA expression dynamics of IL12A, IL12B, IL4, IL27 and EBI3 cytokines genes also evidence the indirect TCDD–mediated modulation of these genes via intrinsic TFs, one of which is ATF3. Conclusion: Exposure to TCDD induces a mechanism of two-stage regulation of the expression of some IL-12 family subunits through primary activation of the aryl hydrocarbon receptor by the TCDD-containing complex followed by ATF3-dependent suppression of their expression. This may result in an abrupt reduction of the anti-tumor response mediated by O and NK cells. The observed increase in ATF3 and decrease in IL-12 following exposure to TCDD are consistent with data on the expression of these genes in tumor-associated macrophages (TAMs). Reliance upon available data that demonstrate a decrease in IL-12 alongside an increase in the expression of other cytokines typical of TAMs confirms the hypothesis that TCDD can shift the phenotype of a macrophage towards a tumor-associated direction. This mechanism may be one of the others underlying TCDD-driven tumor promotion. This work was supported by theRussian Foundation for Basic Research (Russia) (No.12-04-01736 ) and state projects VI.60.1.1 and VI.61.1.2.